IMPLEMENTASI HUKUMAN KEBIRI BAGI PELAKU TINDAK PIDANA KEKERASAN SEKSUAL YANG DILAKUKAN TERHADAP ANAK PERSPEKTIF PERATURAN PEMERINTAH No. 70 Tahun 2020 - TITIN APRIANI (GANEC SWARA, 2024)
The aim of this research is to find out how the castration penalty is implemented for perpetrators of criminal acts of sexual violence committed against children from the perspective of government regulation no. 70 of 2020 and what are the obstacles to not implementing the castration penalty for perpetrators of criminal acts of sexual violence committed against children? This research is library research, namely using data in the form of books, laws, articles, journals and other literature related to the title, while the technique and data collection is by collecting various ideas, theories and concepts from various literature which focuses on the process. comparison between propositions, articles or other laws. The approach methods used in this research are the statutory approach and the conceptual approach. The research results show that the implementation of the castration penalty is still not effective due to various obstacles or factors that prevent law enforcers from implementing the castration penalty